An Analysis of Wayground Application's Use as a Self-Study Tool at SMAN Jatinangor - Ridwan, Revi Nur; Kulsum, Eva Meidi; Fauziyyah, Yulfi Tsaniya (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The integration of digital learning tools has become increasingly vital in modern education, particularly to address issues of student disengagement and lack of motivation. The interactive aspects of Wayground, a game-based learning platform, are designed to increase student engagement and interest. This research aims to investigate Student Perception on the use of Wayground Application as English Learning Media in Class XI-8 at SMAN Jatinangor and to identify the problem they face when using it. A qualitative descriptive method was used involving 21 eleventh grade students as questionnaire respondents and 6 students for interviews. The questionnaire used in this study was adopted from Saputri (2022). Data were collected through a Likert scale questionnaire and semi structured interview. The findings reveal that students generally have a positive perception of Wayground in terms of convenience, excitement, and practicality. Most students agreed that Wayground is easy to use, enjoyable, and helpful in reviewing English material. However, the study also found several technical and affective barriers. Technical issues such as unstable internet and login problem distrupted learning, while affective barriers like time pressure and leaderboard anxiety reduced comfort. Despite these challenges, the interactive and game like nature of Wayground supported student engagement and motivation. The study implies that while Wayground is an effective learning tool, its implementation must consider both technical readines and student affective responses.